Personal names, Hitler, and the Holocaust a socio-onomastic study of genocide and Nazi Germany - Nick, I. M. (Iman Makeba) (Lexington Books, 2019)
During the Third Reich, in the name of national security, the Nazis introduced legislation to quickly and easily mark residents with Jewish heritage to expedite their isolation, deportation, and final extermination. Then as now, the tool used for this lethal demarcation was as innocuous as it was ubiquitous: personal names.